The Influence of a 7-Week Spoken English Course on the Use of Stalling Mechanisms : A Mixed-methods Study of Fluency Development - Aittokumpu, Hanna (My University, 2024)
This MA thesis studies the influence that a 7-week spoken English course has on spoken English development. The study examines the changes in the use of stalling mechanisms as indicators of fluency by investigating both group-level changes and individual variation during the course. The topic of fluency is current in Finland as oral L2 proficiency is considered increasingly more in teaching, with suggestions to include spoken language testing in the matriculation examination having already been made. As of now, Finnish upper secondary schools offer only one spoken English course as an elective (ENA8) that focuses on oral performance, and the aim of this thesis is to investigate how short-term structured instruction influences fluency development during that course. 33 students were examined for their use of stalling mechanisms by analysing speech samples that were recorded before and after the course. The speech samples were transcribed into written format and annotations were made for five stalling mechanisms: silent and filled pauses, drawls, filler words and repetitions. In the group level analysis, the development in the frequency of every stalling mechanism was analysed individually to discover statistically significant changes during the course. This was accompanied by a qualitative study based on extreme case sampling (Dörnyei 2007) to give more detailed insight into individual variation inside the group and short-term gains that are achievable. The results show that group-level changes were mixed. Statistically significant development was observed in the frequency of silent pauses, drawls and Finnish influence on filled pauses, but not in the other stalling mechanisms. Individual variation within the group was substantial, with some students improving their fluency significantly, gaining improvements in the frequency, duration and distribution of silent pauses and other stalling mechanisms, indicating that while group-level development might be harder to detect, individually students can improve greatly during a short timeframe.
Keywords: English, second language acquisition, SLA, fluency, temporal fluency, stalling mechanisms, upper secondary school